2023
DOI: 10.1111/iwj.14605
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for surgical site infection after percutaneous endoscopic lumbar discectomy

Bo Xiao,
Tian‐yi Chen,
Qiang Zhao
et al.

Abstract: The objective of this study was to investigate the risk factors associated with surgical site infection (SSI) after percutaneous endoscopic lumbar discectomy (PELD) in patients with lumbar disc herniation (LDH). A retrospective analysis was performed on a cohort of 335 patients who underwent PELD between January 2016 and January 2023. Data were derived from the Hospital Information System (HIS), and a comprehensive statistical assessment was performed using IBM SPSS Statistics version 25.0. Both univariate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…This study retrospectively analysed the clinical data of 335 patients with surgical site infection (SSI) after percutaneous endoscopic lumbar discectomy (PELD) and concluded that high BMI, diabetes, long‐term use of corticosteroid, long operation time and cerebrospinal fluid leakage were independent risk factors for SSI. 1 We are very grateful for the author’s contribution in this field, but there are still some problems in this study that need to be further explored.…”
mentioning
confidence: 99%
“…This study retrospectively analysed the clinical data of 335 patients with surgical site infection (SSI) after percutaneous endoscopic lumbar discectomy (PELD) and concluded that high BMI, diabetes, long‐term use of corticosteroid, long operation time and cerebrospinal fluid leakage were independent risk factors for SSI. 1 We are very grateful for the author’s contribution in this field, but there are still some problems in this study that need to be further explored.…”
mentioning
confidence: 99%